Sluggish thermochemical basal mantle structures support their long-lived stability - Zhidong Shi; Ross N. Mitchell; Yang Li; Bo Wan; Ling Chen; Peng Peng; Liang Zhao; Lijun Liu; Rixiang Zhu (Nature Communications)
Abstract Large low shear-wave velocity provinces (LLSVPs) in the lowermost mantle are the largest geological structures on Earth, but their origin and age remain highly enigmatic. Geological constraints suggest the stability of the LLSVPs since at least 200 million years ago. Here, we conduct numerical modeling of mantle convection with plate-like behavior that yields a Pacific-like girdle of mantle downwelling which successfully forms two antipodal basal mantle structures similar to the LLSVPs. Our parameterized results optimized to reflect LLSVP features exhibit velocities for the basal mantle structures that are ~ 4 times slower than the ambient mantle if they are thermochemical, while the velocity is similar to the ambient mantle if purely thermal. The sluggish motion of the thermochemical basal mantle structures in our models permits the notion that geological data from hundreds of millions of years ago are related to modern LLSVPs as they are essentially stationary over such time scales.